Implications of oral dysbiosis and HPV infection in head and neck cancer: from molecular and cellular mechanisms to early diagnosis and therapy - Constantin, Marian; Chifiriuc, Mariana Carmen; Mihaescu, Grigore; Vrancianu, Corneliu Ovidiu; Dobre, Elena-Georgiana; Cristian, Roxana-Elena; Bleotu, Coralia; Bertesteanu, Serban Vifor; Grigore, Raluca; Serban, Bogdan; Cirstoiu, Catalin (Frontiers in Oncology, 2023)
Head and neck cancer (HNC) is the sixth most common type of cancer, with more than half a million new cases annually. This review focuses on the role of oral dysbiosis and HPV infection in HNCs, presenting the involved taxons, molecular effectors and pathways, as well as the HPV-associated particularities of genetic and epigenetic changes and of the tumor microenvironment occurred in different stages of tumor development. Oral dysbiosis is associated with the evolution of HNCs, through multiple mechanisms such as inflammation, genotoxins release, modulation of the innate and acquired immune response, carcinogens and anticarcinogens production, generation of oxidative stress, induction of mutations. Thus, novel microbiome-derived biomarkers and interventions could significantly contribute to achieving the desideratum of personalized management of oncologic patients, regarding both early diagnosis and treatment. The results reeported by different studies are not alsways congruent regarding the variations in the abundance of different taxons in HNCs. However, there is a consistent reporting of a higher abundance of Gram-negative species such as Fusobacterium,